Blacks and health care in Brazilian families: a historical and iconographic view - Paulo Fernando de Souza Campos (Universidad de Alicante, 2012)
The present article offers a consideration of the social history in the art of caring. Considered in the long run the study allows us to assess certain facts performed by Brazilian women as first 'child minders'. Evidence comes by means of some photographs used as principal data and from which a cultural and a great interest about care constitutes a faithful debate and is clearly observed. Outcomes indicate that Brazilian historiography on nursing and its main characters: 'nurses', have considered as nursing performances those practices of black women regarding their 'child minding' white families' children for generations up to the XX century. Practices considered effective among Brazilian culture and society, which continue up to the time being in small towns with limited health sources.